CVD growth of large-area InS atomic layers and device applications. Issue 17 (22nd April 2020) - Tu, Chien-Liang; Lin, Kuang-I; Pu, Jiang; Chung, Tsai-Fu; Hsiao, Chien-Nan; Huang, An-Ci; Yang, Jer-Ren; Takenobu, Taishi; Chen, Chang-Hsiao
Abstract : Indium sulfide (InS) atomic layers made by chemical vapor deposition (CVD) are synthesized onto a mica substrate, producing a highly crystalline, large-area, and atomically thin-film InS flakes. Abstract : Group-III monochalcogenides of two-dimensional (2D) layered materials have attracted widespread attention among scientists due to their unique electronic performance and interesting chemical and physical properties. Indium sulfide (InS) is attracting increasing interest from scientists because it has two distinct crystal structures. However, studies on the synthesis of highly crystalline, large-area, and atomically thin-film InS have not been reported thus far. Here, the chemical vapor deposition (CVD) synthesis method of atomic InS crystals has been reported in this paper. The direct chemical vapour phase reaction of metal oxides with chalcogen precursors produces a large-sized hexagonal crystal structure and atomic-thickness InS flakes or films. The InS atomic films are merged with a plurality of triangular InS crystals that are uniform and entire and have surface areas of 1 cm 2 and controllable thicknesses in bilayers or trilayers. The properties of the as-grown highly crystalline samples were characterized by spectroscopic and microscopic measurements. The ion-gel gated InS field-effect transistors (FETs) reveal n-type transport behavior, and have an on–off current ratio of >10 3 and a room-temperature electron mobility of ∼2 cm 2 V −1 s −1 . Moreover, our CVD InS can be transferred from mica to any substrates, so various 2D materials can be reassembled into vertically stacked heterostructures, thus facilitating the development of heterojunctions and exploration of the properties and applications of their interactions.